Molecular Epidemiological Characterization of Respiratory Isolates of Moraxella catarrhalis in a Pediatric Intensive Care Unit - Anne G Matlow; Donald E Low; Gideon Paret; Scott Jarrett; Desmond Bohn; Geoffrey Barker; Jean Boulanger; E Lee Ford-Jones (Canadian Journal of Infectious Diseases)
A perceived increase in the number of isolates of Moraxella catarrhalis from the respiratory secretions of patients intubated in the pediatric intensive care unit prompted a review of the clinical profiles of such patients and restriction enzyme analysis of the strains involved. Over two months, of 192 patients admitted to the unit, 154 were intubated. Of the 46 for whom endotracheal tube specimens were submitted to the laboratory, M catarrhalis was isolated in 12. M catarrhalis was not felt to be a significant respiratory pathogen by the attending medical staff in any of the patients from whom it was isolated. In only two patients (17%) could nosocomial acquisition be firmly invoked. Restriction enzyme analysis of the 12 strains ruled out the presence of an epidemic strain. Isolation of M catarrhalis from intubated children does not necessarily imply pathogenicity nor an outbreak situation.